Recovery of poliovirus epidemic in Iquitos and the Hospital del Niño of Lima - Sellers, Margret I. (1958)
Polioviruses were isolated from cases of paralytic poliomyelitis which occurred in an Iquitos epidemic. From seven faces specimen, one Type I, two Type II, and Type III polioviruses were recovered. Also, on Type III, virus was recovered from a contact who had no clinical symptoms. It is postulated that the source of infection could have been a common water supply recently contaminated with fecal material; this could account for the appearance of all three virus types in a single epidemic. Polioviruses were also isolated fron paralytic poliomyelitus patients in the Hospital del Niño de Lima, Four Type I and one Type III viruses were recovered from these patients.